In vitro antiproliferative activity of Endemic Centaurea kilaea Boiss. against Human Tumor Cell Lines - ŞEN, ALİ; BİTİŞ, LEYLA; ÖZBAŞ, SUNA (AVES PRESS LTD, 2015)
Objective: In this study, it is aimed to determine the active extract on which substance isolation through bioactivity-guided method is to be performed in the future. Therefore, it is planned to reveal the extract exhibiting the highest antiproliferative activity by investigating the activities of heptane (CKH), chloroform (CKC), sub-fractions of active chloroform (CKCSI, CKCSII, CKCSIII) and methanol extracts (CKM) obtained from the aerial parts of Centaurea kilaea Boiss. (Asteraceae) on different cancerous cell lines. Method: Antiproliferative activity was measured against three human cancer cell lines (Hela; cervix adenocarcinoma, MCF-7; breast adenocarcinoma, PC-3; prostate adenocarcinoma) using MTT assay. Results: CKC exhibited the greatest antiproliferative activity with IC50 of 53.07; 68.64 mu g/ml against Hela and MCF-7 cells, respectively, while CKC and CKM showed the highest antitumor activity against PC-3 cell (73.92; 70.11 mu g/ml, respectively). Also, a sub-fraction II of active chloroform extract (CKCSII) demonstrated moderate antiproliferative activity with IC50 values of 60.75 and 60.70 mu g/ml against Hela and MCF-7 cells, respectively. Conclusion: The results show that CKC and CKCSII are good candidates for further bioactivity-guided fractionation in the search for new active antitumor compounds. Also, these findings confirm other results that have been reported in the literature relating to antiproliferative activities of different Centaurea species. Furthermore, active extracts would be tested on different tumor cell lines.
Keywords: Centaurea kilaea; antiproliferative activity; MTT